If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -11) + -6 = 10(1 + -1x) + 6 Reorder the terms: 2(-11 + x) + -6 = 10(1 + -1x) + 6 (-11 * 2 + x * 2) + -6 = 10(1 + -1x) + 6 (-22 + 2x) + -6 = 10(1 + -1x) + 6 Reorder the terms: -22 + -6 + 2x = 10(1 + -1x) + 6 Combine like terms: -22 + -6 = -28 -28 + 2x = 10(1 + -1x) + 6 -28 + 2x = (1 * 10 + -1x * 10) + 6 -28 + 2x = (10 + -10x) + 6 Reorder the terms: -28 + 2x = 10 + 6 + -10x Combine like terms: 10 + 6 = 16 -28 + 2x = 16 + -10x Solving -28 + 2x = 16 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -28 + 2x + 10x = 16 + -10x + 10x Combine like terms: 2x + 10x = 12x -28 + 12x = 16 + -10x + 10x Combine like terms: -10x + 10x = 0 -28 + 12x = 16 + 0 -28 + 12x = 16 Add '28' to each side of the equation. -28 + 28 + 12x = 16 + 28 Combine like terms: -28 + 28 = 0 0 + 12x = 16 + 28 12x = 16 + 28 Combine like terms: 16 + 28 = 44 12x = 44 Divide each side by '12'. x = 3.666666667 Simplifying x = 3.666666667
| (-10)-2= | | 4a+3b+c=19 | | (x[x+12])*2=60*2 | | X=y+wz | | 8x-18y=4 | | 4x^4+64x^2=0 | | 6x+-17=470+10x | | 3(8+x)-3x=4(x-5) | | -5x-9+7x=2 | | 10n+30=60 | | -10n-8=8-8n | | 7(x-4)=5(1+8x) | | 5x+44=4 | | 6w+24=-3(w+4) | | 7n-8=-10n-8 | | 2.6x=17.94 | | x^6-9x^4+24x^2-16=0 | | U-3(6-4y)=4y+2 | | 11x^2+10x+11=0 | | (7)-(-15)= | | (-5)+11= | | 5(1-5x)+1=5x | | 2(-4x-6)=-13 | | -7+8(4r+6)=-215 | | 18x+10y=700 | | -3=7p-5 | | 20n+40=60 | | 12x-15-9x=2x+21 | | 148=250-x | | 3a-9=2a | | 207=-u+10 | | 2b=3b-15 |